Signaling pathways and molecular mediators in metastasis - Fatatis, Alessandro (Springer Netherlands, 2012)
This work presents the most advanced discoveries from translational research laboratories directly involved in identifying molecules and signalling pathways that play an instrumental role in metastasis. In contrast to other works, conventionally focused on a single type of tumour, the various chapters in this book provide a broad perspective of the similarities and discrepancies among the dissemination of several solid malignancies. Through recurrent and overlapping references to molecular mechanisms and mediators, the readers will gain knowledge of the common ground in metastasis from a single source. Finally, an introductory chapter provides a clinical perspective of the problems presented by metastatic tumours for diagnosis and treatment. The work presented here is directed to researchers in tumour biology with a developing interest in metastatic dissemination as well as medical and graduate students seeking to expand and integrate the notions acquired in basic cancer biology and oncology courses.